2021
DOI: 10.3390/polym13040647
|View full text |Cite
|
Sign up to set email alerts
|

A Bibliometric Analysis of the Global Trend of Using Alginate, Gelatine, and Hydroxyapatite for Bone Tissue Regeneration Applications

Abstract: Collecting information from previous investigations and expressing it in a scientometrics study can be a priceless guide to getting a complete overview of a specific research area. The aim of this study is to explore the interrelated connection between alginate, gelatine, and hydroxyapatite within the scope of bone tissue and scaffold. A review of traditional literature with data mining procedures using bibliometric analyses was considered to identify the evolution of the selected research area between 2009 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 86 publications
0
12
0
Order By: Relevance
“…Today, tissue regeneration has become the focus of much interest. [ 1 ] Several possibilities are available to promote the regeneration of damaged tissues. One method to prepare a scaffold aid material is the electrospinning of dilute solutions of carefully selected bio- and biocompatible synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Today, tissue regeneration has become the focus of much interest. [ 1 ] Several possibilities are available to promote the regeneration of damaged tissues. One method to prepare a scaffold aid material is the electrospinning of dilute solutions of carefully selected bio- and biocompatible synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…This trend indicates that research into hydroxyapatite, especially in relation to biomedical applications, is still developing and attracting growing attention in the scientific community. The regenerative medicine approach has become a widely recognized topic in recent decades, especially regarding hydroxyapatite [ 22 , 23 , 24 , 25 ]. Natural and synthetic hydroxyapatite are among the most common materials currently discussed in the context of bone tissue regeneration, due to their bioactivity, low-cost, non-toxicity, and compatibility with the available applications [ 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, bibliometric analysis can be used to identify influential articles that shape medical practice and promote new research ideas. Previous bibliometric studies have pointed out the most highly cited papers in the field of bone regeneration in recent years ( Huang et al, 2020 ), and qualitatively or quantitatively described commonly used polymer materials ( Hussin et al, 2021 ) and artificial extracellular matrices ( Simmons et al, 2020 ) in the field of bone tissue regeneration. Although these studies have identified several classic references in the field of bone tissue regeneration, they focused mainly in the field of materials research, whereas a comprehensive perspective on the related medical concepts is still lacking.…”
Section: Introductionmentioning
confidence: 99%